1994
DOI: 10.1111/j.1745-4530.1994.tb00341.x
|View full text |Cite
|
Sign up to set email alerts
|

NEW MELT CONVEYING MODELS FOR A SINGLE SCREW EXTRUDER1

Abstract: The flow theory in an extruder is fundamental to the study of extrusion technology. Present analytical solutions of the flow theory used in many studies give significant overpredictions of the volumetric flow rate due to erroneous boundary conditions used. Modified flat plate models with and without considering side wall effect and a coaxial cylinder model for Newtonian fluids were derived in this study using new boundary conditions confirmed by Choo et al. (1980). Using experimental data from published litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 7 publications
0
4
0
1
Order By: Relevance
“…To facilitate the analysis of the heat transfer strength at different locations on the steel strip, lines A and B were considered on the surface of the strip (as in Figure 2) [28]. Line A corresponds to the line directly below the center of each row of nozzles; there are eight rows of nozzles in total, so they are lines A1, A2, .…”
Section: Definition Of Parametersmentioning
confidence: 99%
“…To facilitate the analysis of the heat transfer strength at different locations on the steel strip, lines A and B were considered on the surface of the strip (as in Figure 2) [28]. Line A corresponds to the line directly below the center of each row of nozzles; there are eight rows of nozzles in total, so they are lines A1, A2, .…”
Section: Definition Of Parametersmentioning
confidence: 99%
“…Độ chính xác của mô hình là trong phạm vi 25%, tuy nhiên mô hình quá phức tạp để ứng dụng vào thực tế. Tương tự như vậy, Y. Li và F.Hsiel [5] đã tự phát triển mô hình toán mới để tính toán dòng chảy của lưu chất Newton đẳng nhiệt và bất khả nén bên trong máy đùn trục vít đơn. Họ dùng tới 69 phương trình toán học để giải quyết vấn đề.…”
Section: Giới Thiệuunclassified
“…Similarly, in [ 55 ], an analytical model for the flow of Newtonian fluids in finite aspect ratio channels was proposed, and both the pressure-flow rate relation and flow field along the channel height for corn syrup, which can be assumed as a Newtonian fluid, were well predicted. In [ 36 , 56 , 57 , 58 , 59 ], the authors refer to correction factors for pressure and drag flow, as suggested in the case of Newtonian fluids in [ 43 ]; this is a really simple solution for taking into account the limited aspect ratio, and so the influence of both trailing and pushing flights on the flow field. Moreover, it has been shown that at least for the drag flow correction factor, there are no significant differences between the values measured for various polymers and the theoretical values calculated for Newtonian fluids [ 60 , 61 ].…”
Section: Models For the Materials Extrusionmentioning
confidence: 99%